CORRELATION AND REGRESSION ANALYSIS AS A METHOD FOR FORECASTING THE ECONOMIC DEVELOPMENT OF AN ENTERPRISE - Qarshiboyev Xayrullo Qilichovich; Nematov Javoxir Zoxidjon o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: this article discusses correlation and regression analysis as a method of predicting the economic development of an enterprise. Calculation of correlation coefficients allows to determine the closeness and direction of the relationship between the studied indicators. Regression analysis is a natural continuation of correlation analysis and consists in determining the analytical expression of the relationship between the resulting value and factor indicators.